MtMTP2-Facilitated Zinc Transport Into Intracellular Compartments Is Essential for Nodule Development in Medicago truncatula - León-Mediavilla, Javier; Senovilla, Marta; Montiel, Jesús; Gil-Díez, Patricia; Saez, Ángela; Kryvoruchko, Igor S.; Reguera, María; Udvardi, Michael K.; Imperial, Juan; González-Guerrero, Manuel (Frontiers in Plant Science, 2018)
Zinc (Zn) is an essential nutrient for plants that is involved in almost every biological process. This includes symbiotic nitrogen fixation, a process carried out by endosymbiotic bacteria (rhizobia) living within differentiated plant cells of legume root nodules. Zn transport in nodules involves delivery from the root, via the vasculature, release into the apoplast and uptake into nodule cells. Once in the cytosol, Zn can be used directly by cytosolic proteins or delivered into organelles, including symbiosomes of infected cells, by zinc efflux transporters. Medicago truncatula MtMTP2 (Medtr4g064893) is a nodule-induced Zn-efflux protein that was localized to an intracellular compartment in root epidermal and endodermal cells, as well as in nodule cells. Although the MtMTP2 gene is expressed in roots, shoots, and nodules, mtp2 mutants exhibited growth defects only under symbiotic, nitrogen-fixing conditions. Loss of MtMTP2 function resulted in altered nodule development, defects in bacteroid differentiation, and severe reduction of nitrogenase activity. The results presented here support a role of MtMTP2 in intracellular compartmentation of Zn, which is required for effective symbiotic nitrogen fixation in M. truncatula.